Food is Medicine: A Review of Current Government School Lunch Policies Across America - Jaeyoon Park (Undergraduate Research Journal for the Human Sciences, 2024)
Nutritious school meals play a critical role in children’s overall well-being along with several other factors like family consumption and peer influence. However, there are various problems associated with school lunches: the inability of low-income families to afford nutritious meals, insufficient funding for high-quality lunches, the need for more awareness about proper nutrition, and more. Although several national programs and governmental policies are promoting healthy lunches for child nutrition care, such as the National School Lunch Program (NSLP), School Breakfast Program (SBP), Special Milk Program (SMP), National Farm to School organization, and more, many public schools still do not provide nutritional meals and do not adhere to dietary guidelines, inevitably leading to substandard school food quality. Thus, there is a need for the federal government to consider allocating more funds to create an environment that promotes nutritious diets for youth while also providing oversight to the programs that already exist as they will improve the short-term and long-term health of students.
Keywords: Nutrition; Food; USDA; NSLP; SBP; school lunch